Diel fluctuations in solute distributions and biogeochemical cycling in a hypersaline microbial mat from Shark Bay,WA - Pages, Anais; Welsh, D.; Teasdate, P.; Grice, Kliti; Vacher, M.; Bennett, W.; Visscher, P. (Elsevier Science B.V., 2014)
Studying modern microbial mats can provide insights into how microbial communities interact with biogeochemical cycles. High-resolution, two-dimensional distributions of porewater analytes were determined in the upper three layers of a modern microbial mat from Nilemah, Shark Bay, Western Australia, using colorimetric diffusive equilibration in thin film (DET) and diffusive gradients in thin film (DGT) techniques. The colorimetric DET and DGT techniques were used to investigate the co-distributions of sulfide, iron(II), and phosphate and the alkalinity. Two-dimensional distributions of sulfide, iron(II) and phosphate showed a high degree of spatial heterogeneity under both light and dark conditions. However, average concentration profiles showed a clear shift in overall redox conditions between light and dark conditions. During light deployments, iron(II) and sulfide concentrations were generally low throughout the entire microbial mat. In contrast, during dark deployments, when anoxic conditions prevailed, higher concentrations of iron(II) and sulfide were observed and the sulfide boundary migrated towards the upper layer of the mat. Similar to the iron(II) profile, the phosphate profile showed an increase in concentration at night, suggesting that phosphate was released through the dissolution of iron–phosphate complexes under anoxic conditions.However, two-dimensional distributions revealed that hot spots of phosphate and iron(II) did not coincide, suggesting that porewater phosphate was mainly regulated by diel metabolic changes in the mat. Alkalinity profiles also demonstrated an increase in concentration at night, probably related to high rates of sulfate reduction under dark conditions. Complimentary microelectrode measurements of oxygen and sulfide confirmed that light-limited microbial communities play a significant role in regulating porewater solute concentrations, especially through photosynthetic activity that supports rapid re-oxidation of sulfide during the day. Sulfide was not detected in the upper layers (ca. 4 mm) of the mat by microelectrode measurements, but was found at those depths by the time-integratedDGT measurements. Complimentary silver foil deployments also showed a 2D distribution of sulfate-reducing activity occurring under oxic conditions in the top layers. DGT, O2 and sulfide microelectrode profiles and silver foils confirmed hotspots of sulfide production coinciding with cyanobacterial photosynthesis. Two-dimensional porewater analyte distributions showed significant small-scale heterogeneity, highlighting the complexity of such dynamic ecosystems and the advantage of two-dimensional methods.